Composite solid electrolyte and preparation and application thereof
By using the ice template method in solid lithium-ion batteries and filling with polyion liquid, composite solid electrolyte is formed, the problems of low conductivity and insufficient structural stability are solved, and high electrochemical performance and mechanical strength are achieved. Take into account both.
Patent Information
- Application Number
- CN202411535153.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
Existing solid-state lithium-ion batteries have low conductivity and challenges in both structural stability and performance.
Using melamine sponge as support, a porous ceramic sheet with a continuous pore structure was prepared by the ice template method, and a polyion liquid solution was filled into the porous ceramic sheet by the titration permeation method to form a composite solid electrolyte.
The ion conductivity and lithium ion migration number of the composite solid electrolyte are improved, the electrochemical performance and mechanical strength are enhanced, and the cycle stability is high.
Smart Images

Figure CN119400944A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a composite solid electrolyte, a preparation method and application thereof in solid-state lithium ion batteries. Background Art
[0002] Lithium-ion batteries are widely used in electronic devices, electric vehicles, and large-capacity energy storage systems due to their relatively high power / energy density. Traditional lithium-ion batteries use liquid electrolytes with low resistance. Although liquid electrolytes have the advantages of high conductivity and excellent wettability of the electrode surface, they have safety hazards such as leakage and spontaneous combustion during use. Compared with liquid electrolytes, solid electrolytes tend to reduce the total weight and volume of the battery, thereby increasing its mass energy density and volume energy density, and solid electrolytes are non-flammable. As an important component of solid-state batteries, the performance of solid electrolytes plays a vital role in the electrochemical performance of the battery.
[0003] Common solid electrolytes include inorganic solid electrolytes and polymer electrolytes. Inorganic solid electrolytes mainly include NASICON type, perovskite type, garnet type, etc. The advantages of inorganic solid electrolytes are excellent stability and a wide electrochemical working window, but different types of inorganic solid electrolytes have their own advantages and disadvantages, and it is impossible to take into account all the advantages, and there are technical barriers in reducing the interface impedance between the electrode. Polymer electrolytes are an electrolyte material formed by compounding lithium salts into a polymer matrix. The polymer matrix includes polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyacrylonitrile (PAN), polyvinylidene fluoride (PVDF), polypropylene carbonate (PPC), etc. Because polymer electrolytes are soft and flexible, they are easier to implement in commercial applications; but most polymer electrolytes have low ion conductivity (10 -8 -10 -5 S cm -1 ) and electrochemical window (<5V vs.Li + / Li) is limited and other issues.
[0004] Combining organic and inorganic solid electrolytes to construct composite solid electrolytes, which have both the high strength characteristics of inorganic solid materials and the flexibility of polymer materials, has become an effective way to deal with the above problems. The most common measure is to disperse zero-dimensional inorganic particles or one-dimensional inorganic fibers as fillers in the polymer skeleton by mechanical mixing. The addition of inorganic fillers can reduce the crystallinity of the polymer to a certain extent and improve the conductivity of the polymer matrix. However, the addition of such fillers has limited effect on improving the conductivity of the composite electrolyte, and blindly adding a large amount will cause the particles or fibers to tend to agglomerate, and the conductivity of the composite electrolyte is difficult to be further improved, and may even decrease. Therefore, the preparation of a composite solid electrolyte with a reasonable structure is the key to solving the corresponding problems.
[0005] Chinese patent CN 116207337 A discloses a composite solid electrolyte and its preparation method, wherein inorganic ceramic powder is mixed with sodium chloride as a pore-forming agent, and a LATP skeleton with a 3D network structure is prepared without adding a binder. A 3D composite solid electrolyte is formed by adding a PIL polymer thereto. The 3D network structure provides a fast transmission channel for lithium ions, so that the ionic conductivity of the obtained material reaches 1.59×10 -4 S cm -1 However, further research found that this scheme uses NaCl as a template. When the amount of NaCl is small, although the LATP flake rate is high, the interconnecting pores cannot be effectively formed inside the skeleton; and when the amount of NaCl is increased, although the porous structure is easy to form, it will cause the collapse of the LATP skeleton, so it is difficult to take into account both structural stability and material performance. Therefore, it is necessary to conduct more in-depth research on the preparation of the LATP skeleton with a network structure. Summary of the invention
[0006] The purpose of the present invention is to solve the deficiencies in the prior art and to provide a composite solid electrolyte and its preparation and application. The present application uses melamine sponge as a structural support and utilizes an ice template method to prepare a porous ceramic sheet with a continuous pore structure. The polyionic liquid solution is then filled into the porous ceramic sheet based on a titration osmosis method. This scheme can reduce the crystallinity of the polymer and obtain a composite solid electrolyte with a rapid lithium ion transmission channel and high mechanical strength. The obtained electrolyte material has a high ionic conductivity, and the solid battery prepared on this basis has excellent electrochemical properties.
[0007] The specific technical solution of the present invention is: a method for preparing a composite solid electrolyte, comprising the following steps:
[0008] 1) immersing the melamine sponge in the slurry prepared by mixing the pore-forming agent, taking it out and freezing it in liquid nitrogen to obtain a mixed electrolyte disc, and drying it;
[0009] 2) sintering the mixed electrolyte disc and grinding it into a thin porous ceramic sheet after sintering;
[0010] 3) filtering the polyionic liquid, washing the precipitate and drying it to obtain a polyionic liquid powder, mixing the polyionic liquid powder with a lithium salt in an organic solvent, and stirring to obtain a polyionic liquid solution;
[0011] 4) The polyionic liquid solution is filled into the porous ceramic sheet by using a titration osmosis method, and then dried to obtain a composite solid electrolyte.
[0012] Furthermore, in step 1), the pore-forming agent is a mixture of inorganic ceramic powder and deionized water, the mass ratio of the inorganic ceramic powder to deionized water is 0.9-1.4:1.5, the pore-forming agent and the binder are mixed and stirred to obtain a slurry, and the freezing and setting time in liquid nitrogen is 25-40s.
[0013] Preferably, in step 1), the mass ratio of the inorganic ceramic powder to deionized water is 1.2:1.5.
[0014] Furthermore, the inorganic ceramic powder is Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 or Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 Any one of .
[0015] Furthermore, in step 2), the sintering temperature is 750-840°C, the holding time is 2-6h, and the heating rate is 3-5°C min -1 .
[0016] Furthermore, in step 2), the thickness of the porous ceramic sheet is 800-950 μm.
[0017] Furthermore, in step 3), the polyionic liquid is any one of poly(1-ethyl-3-acrylate) imidazole bis(trifluoromethanesulfonyl)imide salt, PEO (polyethylene oxide), PVDF-HFP (poly(vinylidene fluoride-co-hexafluoropropylene)) or PVDF (polyvinylidene fluoride); and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0018] Furthermore, in step 3), the mass ratio of the polyionic liquid powder to the lithium salt is 1 to 3:1.
[0019] The present application also provides a composite solid electrolyte prepared by the above method.
[0020] The present application also provides a solid-state lithium metal battery, which is obtained by assembling the above-mentioned composite solid electrolyte with positive and negative electrode materials, wherein the positive electrode material is lithium iron phosphate, and the composite solid electrolyte is arranged between the negative electrode material and the positive electrode material.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] 1. This application uses melamine sponge as a support, prepares porous LATP ceramic sheets by ice template method, and then fills PIL solution into the porous ceramics by titration infiltration method to form a composite solid electrolyte. The overall preparation process is simple and easy to operate;
[0023] 2. The porous LATP ceramic sheet prepared by the ice template method has high mechanical strength, stable structure and is not easy to collapse. It has continuously arranged microporous channels inside. As a rigid skeleton, it can inhibit the growth of lithium dendrites. The polymer and LATP form a continuous channel network, which is beneficial to the Li + The composite solid electrolyte has a high ionic conductivity (0.81×10 -3 S cm -1 ), and the lithium ion migration number (t Li + ) has been greatly improved, reaching 0.79;
[0024] 3. The solid-state lithium metal Li||Li symmetric battery assembled based on the composite solid electrolyte prepared in this application has excellent electrochemical performance and high cycle stability, and can maintain 110mAh g at a current density of 0.2C. -1 The discharge capacity is stable for more than 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 (a) The small picture is an optical photograph of the porous LATP ceramic sheet prepared in Example 1; (b) The small picture is a cross-sectional SEM image of the porous LATP ceramic sheet prepared in Example 1; (c) The small picture is a planar SEM image of the composite solid electrolyte LH-1;
[0026] Figure 2 The conductivity and lithium ion migration number data of the composite solid electrolyte LH-1 prepared in Example 1: (a) The small figure is a graph showing the variation of bulk impedance of the composite solid electrolyte LH-1 with temperature; (b) The small figure is a graph showing the variation of conductivity of the composite solid electrolyte LH-1 with temperature; (cd) The small figures are respectively the chronoamperometric curve of the Li|Li symmetric battery assembled based on the composite solid electrolyte LH-1 at a constant voltage of 10 mV and the AC impedance diagrams before and after polarization;
[0027] Figure 3The small figure (a) is the electrochemical window diagram of the composite solid electrolyte LH-1, and the small figure (b) is the electrochemical performance diagram of the solid lithium metal Li||Li symmetric battery prepared in Example 1;
[0028] Figure 4 The small figure (a) is the charge and discharge curve of the solid-state lithium metal Li||Li symmetric battery assembled in Example 1 at a rate of 0.2C at the 1st, 10th, 50th and 100th cycles; the small figure (b) is the cycle efficiency diagram of the solid-state lithium metal Li||Li symmetric battery assembled in Example 1 at a constant current charge and discharge at 0.2C;
[0029] Figure 5 This is a statistical graph of the ionic conductivity of composite solid electrolytes LH-1, LH-2, LH-3, and LH-4 at room temperature 25°C. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0031] Example 1
[0032] In this embodiment, a composite solid electrolyte is prepared by an ice template method, and the specific preparation process is as follows:
[0033] 1) LATP and deionized water were mixed in a mass ratio of 1.2:1.5, 5 wt % of polyethylene glycol (PEGMw200) was added as a binder, and the mixture was stirred at room temperature for 10 h to obtain a uniform LATP suspension.
[0034] 2) Cut the melamine sponge into discs with a thickness of 3 mm and a diameter of 17 mm for later use. The melamine sponge plays a supporting role. Immerse the sponge disc in the LATP suspension for 20 seconds. After taking it out, freeze the sponge soaked in the suspension with liquid nitrogen for 30 seconds to fix it, so that ice crystals grow continuously from the bottom to the top to obtain a mixed electrolyte disc. Then place it in a freeze dryer and dry it for 14 hours to remove the ice crystals. -1 The heating rate was maintained at 810 °C for 3 h to remove the sponge matrix and PEG. After sintering, the porous LATP ceramic sheet with a thickness of 850 μm was polished with sandpaper.
[0035] 3) Preparation of PIL solution: add 1 g of poly (1-ethyl-3-acrylate) imidazolium bromide (PEMEImBr) to 1 L of deionized water, stir for 20 h, add 2 g of lithium bis(trifluoromethylsulfonyl)imide (LiTFSI) and continue stirring for 24 h. After ion exchange, PEMEImTFSI (PIL) polyionic liquid is obtained, and a white precipitate is obtained by filtration. The precipitate is washed with deionized water and dried in a vacuum oven at 60°C for 8 h to obtain PIL powder. PIL powder and LiTFSI are mixed in a mass ratio of 2:1, and an appropriate amount of N-methylpyrrolidine (NMP, preferably enough to cover the mixture of PIL and LiTFSI) is added. The mixture is stirred for 10 h to obtain a PIL solution.
[0036] 4) In a glove box filled with argon, 0.2 mL of PIL solution was dropped onto the surface of the porous LATP ceramic sheet using a syringe, and allowed to stand for 30 min to allow it to fully infiltrate into the pores of the porous LATP ceramic sheet. It was then placed in a heating chamber filled with argon and dried at 80 °C for 6 h to obtain a composite solid electrolyte, recorded as LH-1.
[0037] The solid-state lithium metal battery assembly method is as follows:
[0038] Lithium iron phosphate powder, Super P (conductive carbon black) and PVDF (polyvinylidene fluoride) powder were weighed in a mass ratio of 8:1:1, ground to make the three evenly mixed, added an appropriate amount of N-methylpyrrolidone to make a slurry, and the slurry was evenly coated on the aluminum foil current collector, vacuum dried at 80°C for 24 hours, and sliced to obtain the LFP positive electrode. The solid-state lithium metal battery device was assembled in the order of positive electrode shell, LFP positive electrode sheet, composite solid electrolyte LH-1, metal lithium, steel sheet, shrapnel and negative electrode shell.
[0039] Example 2
[0040] The only difference between Example 2 and Example 1 is that in step 1), the mass ratio of LATP to deionized water is 0.9:1.5, and the remaining steps and processes are the same. The obtained composite solid electrolyte is recorded as LH-2.
[0041] Example 3
[0042] The only difference between Example 3 and Example 1 is that in step 1), the mass ratio of deionized water to LATP is 1:1.5, and the remaining steps and processes are the same. The obtained composite solid electrolyte is recorded as LH-3.
[0043] Example 4
[0044] The only difference between Example 4 and Example 1 is that in step 1), the mass ratio of deionized water to LATP is 1.4:1.5, and the remaining steps and processes are the same. The obtained composite solid electrolyte is recorded as LH-4.
[0045] Related performance tests
[0046] Figure 1 In the figure (a), the optical photograph of the porous LATP ceramic sheet prepared in Example 1 is shown. From the figure, the surface of the porous LATP ceramic sheet is relatively uniform and regular; in the figure (b), the cross-sectional SEM image of the porous LATP ceramic sheet prepared in Example 1 is shown. From the figure, it can be seen that the porous LATP ceramic sheet prepared by the ice template method has continuous channels, which can provide continuous transmission channels for lithium ions; in the figure (c), the planar SEM image of the composite solid electrolyte LH-1 is shown. It can be seen that the PIL has infiltrated the porous LATP ceramic sheet and covered the surface with a layer of polymer film.
[0047] Figure 2 The middle (a) panel shows the variation of bulk impedance of the composite solid electrolyte LH-1 with temperature. The lithium ion conductivity of LH-1 is calculated by the formula, and it is known that the ion conductivity of the composite solid electrolyte LH-1 at room temperature of 25°C reaches 0.81×10 -3 S cm -1 ( Figure 2 (b) inset), and the conductivity reached 10 in the entire test temperature range. -4 S cm -1 above; from Figure 2 As shown in the middle (d) panel, the lithium ion migration number (t Li + ) has been greatly improved, reaching 0.79.
[0048] Figure 3 (a) is the electrochemical window diagram of the composite solid electrolyte LH-1, with a voltage range of 2-4.9 V. (b) is the electrochemical performance diagram of the solid lithium metal Li||Li symmetric battery prepared in Example 1. It can be seen from the figure that the Li|Li symmetric battery has a voltage range of 2-4.9 V. -2 It can run stably for more than 800 hours.
[0049] Figure 4 The small figure (a) is the charge and discharge curve of the solid-state lithium metal Li||Li symmetric battery assembled in Example 1 at 0.2C rate at the 1st, 10th, 50th and 100th cycles; the small figure (b) is the cycle efficiency diagram of the solid-state lithium metal Li||Li symmetric battery assembled in Example 1 under constant current charge and discharge at 0.2C; It can be seen from the two small figures that the solid-state lithium metal Li||Li symmetric battery prepared in Example 1 can maintain 110mAh g at a current density of 0.2C. -1 The discharge capacity is stable for more than 100 cycles.
[0050] The ionic conductivity of the composite solid electrolytes LH-1, LH-2, LH-3 and LH-4 prepared in Examples 1-4 at room temperature 25°C was calculated. Figure 5 ) found that the conductivity of the composite solid electrolyte first increased with the increase of LATP content. The excellent conductivity was due to the continuous channels in the porous LATP skeleton synthesized by the ice template method, which increased the contact area between LATP and PIL, making LATP have lower grain boundary resistance and providing faster continuous Li + However, when the LATP content increases further, the LATP particles tend to agglomerate, which eventually leads to a decrease in the ionic conductivity of LH-4.
[0051] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a composite solid electrolyte, characterized in that: The steps include: 1) immersing the melamine sponge in the slurry prepared by mixing the pore-forming agent, taking it out and freezing it in liquid nitrogen to obtain a mixed electrolyte disc, and drying it; 2) sintering the mixed electrolyte disc and grinding it into a thin porous ceramic sheet after sintering; 3) filtering the polyionic liquid, washing the precipitate and drying it to obtain a polyionic liquid powder, mixing the polyionic liquid powder with a lithium salt in an organic solvent, and stirring to obtain a polyionic liquid solution; 4) The polyionic liquid solution is filled into the porous ceramic sheet by using a titration osmosis method, and then dried to obtain a composite solid electrolyte.
2. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step 1), the pore former is a mixture of inorganic ceramic powder and deionized water, the mass ratio of the inorganic ceramic powder to deionized water is 0.9-1.4:1.5, the pore former and the binder are mixed and stirred to obtain a slurry, and the freezing time in liquid nitrogen is 25-40s.
3. The method for preparing a composite solid electrolyte according to claim 2, characterized in that: In step 1), the mass ratio of the inorganic ceramic powder to deionized water is 1.2:1.
5.
4. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: The inorganic ceramic powder is Li 1.5 Al 0.5 Ge 1.5 (PO4)3 or Li 1.3 Al 0.3 Ti 1.7 Any one of (PO4)3.
5. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step 2), the sintering temperature is 750-840°C, the holding time is 2-6h, and the heating rate is 3-5°C min -1 .
6. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step 2), the thickness of the porous ceramic sheet is 800-950 μm.
7. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step 3), the polyionic liquid is any one of poly(1-ethyl-3-acrylate) imidazole bis(trifluoromethanesulfonyl)imide salt, PEO, PVDF-HFP or PVDF; and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
8. The method for preparing a composite solid electrolyte according to claim 1, characterized in that: In step 3), the mass ratio of the polyionic liquid powder to the lithium salt is 1 to 3:
1.
9. A composite solid electrolyte, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. A solid-state lithium metal battery, characterized in that: It comprises the composite solid electrolyte as claimed in claim 9, a negative electrode material and a positive electrode material, wherein the composite solid electrolyte is arranged between the negative electrode material and the positive electrode material.
Citation Information
Patent Citations
Composite solid electrolyte with two surfaces and preparation method thereof
CN112151859A
Polyion liquid / active ceramic composite electrolyte and preparation method thereof
CN113178618A
High-ionic-conductivity composite solid electrolyte, preparation method and application
CN114883638A
Composite solid electrolyte, preparation method thereof and solid lithium metal battery
CN116207337A
Self-supporting composite solid electrolyte as well as preparation method and application thereof
CN117728004A
Cited By
Solid electrolyte with high ionic conductivity and preparation method thereof
CN121307162A